Use of Doppler ultrasonography in embryo transfer programs: feasibility and field results - Pugliesi, Guilherme; Melo, Gabriela Dalmaso de; Ataide, Gilmar Arantes; Gontijo Pellegrino, Carlos Augusto; Silva, Julio Barboza; Rocha, Cecilia Constantino; Motta, Igor Garcia; Moraes Vasconcelos, Jose Luiz [UNESP]; Binelli, Mario (Brazilian Coll Animal Reproduction, 2018)
The intensive use of Doppler ultrasonography in several studies in the last decade allowed the characterization of vascular perfusion and the estimation of function of the reproductive organs and tissues along the estrous cycle and pregnancy in cattle. We aim to discuss the possibility of using Doppler imaging and to explore the potential of its inclusion in reproductive programs in cattle industry. Recent studies in dairy and beef cows indicated a high accuracy and sensitivity when Doppler ultrasonography is used to evaluate corpus luteum function and to diagnosis pregnancy between days 20 and 22. Moreover, resynchronization programs starting 5 to 7 days after timed embryo transfer (FTET) coupled with early pregnancy diagnosis were developed for beef cattle, and have been implemented in commercial embryo transfer programs. These strategies allow a reduction in the interval between two FTET from 40 to 24 days and may improve the gains in reproductive efficiency when compared to traditional programs than begin resynchronization after the pregnancy diagnosis at 30 days. A second alternative to use Doppler imaging is the evaluation of luteal blood perfusion at the time of embryo transfer for selection of recipients with greater receptivity potential. This may increases fertility in FTET, as embryos would not be transferred to females with non-functional CL, and in cases with recipients surplus, females with higher receptivity would be prioritized.
Keywords: blood flow; corpus luteum; pregnancy; Uterus